The myth of the toad‐eating frog. Issue 7 (10th October 2008) - Shine, Richard; Greenlees, Matthew; Crossland, Michael; Nelson, David
Abstract : In 2005, news media widely reported the discovery that a native Australian frog species, Litoria dahlii, could consume the normally toxic tadpoles of invasive cane toads (Bufo marinus ) without ill effects, and might therefore be helpful in controlling these troublesome pests. Our experimental studies show that, contrary to the story, L dahlii is just as vulnerable to toad toxins as are other native frog species. So, why did the story spread so widely, and what does this tell us about the power of myth in public debates about conservation issues?